(untitled) (Research, Society and Development, 2021)
Aim: to analyze the networks production and the interface with the public-private sector in the care for people with chronic respiratory diseases. Material and methods: used the qualitative exploratory approach, in which data were collected through guided by a semi-structured script. The locations chosen for data collection were the Family Health Units, which are located in a Sanitary District of Salvador-Bahia. The sample consists of 15 participants chosen by saturation of responses. Results: The care networks are also built by the user, constituting the living texture and the public-private part of this network from the paths taken by the user between services of different natures so that they can solve their demands in the act of weaving their careers. networks themselves, there is a deficit of interlocution in services, and the itinerary built between public-private can be produced by health professionals. Conclusion: The health care networks present organizational problems, which interferes with integral care and its continuity, and that there is an interface between the public and the private to meet the needs of users.